Some inequalities on the eigenvalues and spreads associated with a graph - Li, Rao (Utilitas Mathematica, 2013)
In this note, we present some inequalities on the eigenvalues, Laplacian eigenvalues, signless Laplacian eigenvalues, and distance eigenvalues of a graph. We also present some bounds on spreads, Laplacian spreads, signless Laplacian spreads, and distance spreads of a graph.